The role of intracranial venous hypertension in the pathogenesis of hydrocephalus - Norrell, Horace A.; Wilson, Charles B.; Bertan, Vural (The Turkish Journal of Pediatrics, 1968)
We have shown that sagittal sinus venous pressure is frequently elevated in cases of infantile hydrocephalus. Of more importance, we found that increasing intraventricular pressure is accompanied by a parallel rise in sagittal sinus venous pressure, almost exclusively in children with myelomeningoceles. This rise in pressure is probably related to a dynamic block of the malpositioned transverse sinuses accompanying the Arnold-Chiari malformation. We suspect a structural obstruction of the venous sinus, not related to intracranial pressure, in the group of children with elevated baseline SSVP not rising in response to saline infusion. We suggest that venous hypertension may have a primary etiologic role in certain cases of infantile hydrocephalus.